2018
DOI: 10.2478/psicolj-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

Recursive Partitioning Methods for Data Imputation in the Context of Item Response Theory: A Monte Carlo Simulation

Abstract: Missing data is a common problem faced by psychometricians and measurement professionals. To address this issue, there are a number of techniques that have been proposed to handle missing data regarding Item Response Theory. These methods include several types of data imputation methods -corrected item mean substitution imputation, response function imputation, multiple imputation, and the EM algorithm, as well as approaches that do not rely on the imputation of missing values -treating the item as not present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…However, less proficient respondents were unable to distinguish items well and except for skipping unknown items, they might also skip items that they could have answered correctly if they spent enough time on the items. Unlike MAR, NMAR occurs when missing data are directly related to the value of the missing variable itself (Edwards & Finch, 2018). For example, items that respondents are expected to answer incorrectly are more likely to be skipped.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…However, less proficient respondents were unable to distinguish items well and except for skipping unknown items, they might also skip items that they could have answered correctly if they spent enough time on the items. Unlike MAR, NMAR occurs when missing data are directly related to the value of the missing variable itself (Edwards & Finch, 2018). For example, items that respondents are expected to answer incorrectly are more likely to be skipped.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, previous research showed that FIML tends to yield unbiased parameter estimates when the type of missingness is either MCAR or MAR (Enders & Bandalos, 2001). Finally, FIML is the default missing data technique in most IRT software programs, making this method convenient to use in practice (Edwards & Finch, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations